Anthropogenic climate change doubled the frequency of compound drought and heatwaves in low-income regions - Boen Zhang; Shuo Wang; Louise Slater (Communications Earth & Environment)
Abstract Compound drought-heatwaves have garnered widespread attention due to their catastrophic consequences. However, little research has investigated inequalities in exposure to compound drought-heatwaves under climate change. Here, we reveal a significant disparity between low-income and high-income regions in terms of global compound drought-heatwave occurrence using observations and climate models. We find that low-income regions experienced a 377% [351–403%] increase in the frequency of compound drought-heatwaves from 1981 to 2020, which is twice as fast as the increase observed in high-income regions (184% [153–204%]). This inequality is largely attributed to a similar disparity in drought occurrence rather than heatwave occurrence. Climate change attribution suggests that anthropogenic warming has doubled the frequency of compound drought-heatwaves over 31% [14–50%] of low-income regions, compared to only 4.7% [0.9–8.3%] of high-income regions. The frequency of compound drought-heatwaves would not have increased in low-income regions without anthropogenic climate change but would still have risen in high-income regions.